Mothers' Willingness to Use Breastfeeding Supports: Evidence From Formally Employed Mothers in Central Kenya. (14th June 2022) - Ickes, Scott; Lemein, Hellen; Mason, Anna; Kinyua, Joyceline; Nduati, Ruth; Singa, Benson; Denno, Donna; Ithondeka, Angeline; Walson, Judd
Abstract: Objectives: We aimed to understand mothers' willingness to use currently available breastfeeding supports at their workplaces and expected use if new supports were made available. Methods: We conducted a cross-sectional survey with closed and open-ended questions among 300 formally employed mothers of children ages 12 months and younger at two public healthcare facilities in Naivasha, Kenya, and community transportation sites for commercials farms and hotels. We surveyed maternal demographics, healthcare access and utilization, employment history, mother's awareness of current breastfeeding supports at her workplace, and self-reported willingness to use additional breastfeeding supports. Results: The most available reported current workplace supports were schedule flexibility to arrive late or leave early (87.8%), opportunity to return home during lunch (24.7%), and company-funded daycare in the community (7.6%). Few mothers reported availability of lactation rooms (3.6%), on-site daycare (3.3%), transportation to breastfeed during lunch (2.3%), a refrigerator for expressed milk (1.6%), a manual breastmilk pump (1.0%), or an electric breastmilk pump (0.7%). When asked about willingness to use if made available, mothers were most willing (>80% agreement) to use flexible work schedules to arrive late, leave early, break during lunch, and use transportation to return home to breastfeed. A moderate proportion were willing to use on-site daycare (63.8%), company-funded community daycare (56.9%), on-site lactation rooms (60.5%), refrigeration for expressed milk (49.3%), manual (40.5%) and electric pumps (27.6%). Conclusions: The currently available workplace breastfeeding supports do not align well with mothers' demand for or willingness to use certain supports. Current resources – such as on-site daycare – are rare at workplaces but are among the most demanded supports by mothers. Lactation rooms are also rare, but demanded less by mothers than on-site daycare or flexible work schedules. Funding Sources: Supported by the National Institutes of Health Fogarty International Center.